THE ORIGINAL DOCUMENTS PROJECT UNDERTAKEN BY THE BRITISH RECORDS ASSOCIATION AND THE SOLICITOR'S REGULATORY AUTHORITY/LAW SOCIETY. Issue 130 (April 2015) - Alcock, Nat; Baker, Penelope
Abstract : Between spring 2012 and autumn 2014, the British Records Association (BRA) undertook a project with the Solicitor's Regulatory Authority (SRA) under the aegis of the Law Society, to identify historical documents held by the SRA in its intervention archive, and arrange for their transfer to appropriate record offices. This report sets out the process, findings and outcomes of the project.